Survey on antibiotic regimens for necrotizing enterocolitis prescribed by Chinese pediatricians in 2020 - Yu He; Yuan Shi; Luquan Li; Zhongyao Zhang; Zhengli Wang; Lei Bao (BMJ Publishing Group, 2021)
Background Necrotizing enterocolitis (NEC) is a serious intestinal inflammatory disease in neonates, and intravenous antibiotics constitute the main therapeutic strategy. Studies have shown that substantial variation in the selection of antibiotic regimens for NEC remains in many countries. The variability in antibiotic therapy selection in China is unclear.Methods A cross-sectional study using an online questionnaire regarding antibiotic regimens for NEC was conducted among pediatricians working in tertiary hospitals in China.Results A total of 284 pediatricians from 29 provinces completed the survey; 37.9% of them administered one antibiotic, 56.7% administered two antibiotics and 2.4% administered three antibiotics. The top three single-antibiotic regimens for NEC were beta-lactamase inhibitors (n=66, 41.5%), carbapenems (n=46, 28.9%) and cephalosporins (n=33, 20.8%). Twenty combinations of two antibiotics were identified, and the top three combinations were beta-lactamase inhibitors and antianaerobic agents (n=49, 19.6%), carbapenems and glycopeptides (n=42, 16.8%), and cephalosporins and antianaerobic agents (n=37, 14.8%). Regarding the therapeutic duration of antibiotic treatment, 77.5% (n=220) of the pediatricians chose 5-10 days for stage II NEC, and 79.6% (n=226) chose 7-14 days for stage III NEC. Forty-three percent (n=122) of the respondents preferred to use carbapenems when NEC was diagnosed, and 83.3% (n=135) adjusted the antibiotics to carbapenems if a patient's medical condition deteriorated or if the therapeutic efficacy was poor.Conclusion This survey revealed that carbapenems were the most common antibiotics selected when NEC was diagnosed or a patient's condition deteriorated, but the duration of the course of treatment for NEC varied substantially among doctors.